2000
DOI: 10.1212/wnl.54.6.1316
|View full text |Cite
|
Sign up to set email alerts
|

Head injury and the risk of AD in the MIRAGE study

Abstract: Head injury is a risk factor for AD. The magnitude of the risk is proportional to severity and heightened among first-degree relatives of AD patients. The influence of head injury on the risk of AD appears to be greater among persons lacking APOE-epsilon4 compared with those having one or two epsilon4 alleles, suggesting that these risk factors may have a common biologic underpinning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
284
5
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(306 citation statements)
references
References 44 publications
14
284
5
3
Order By: Relevance
“…Loss of PDE4A from spines with advancing age leads to dysregulation of cAMP-Ca 2+ signaling and increased kinase phosphorylation of tau in pyramidal cell circuits. However, it has long been appreciated that head injury is also a significant risk factor for AD (39) as well as CTE (34,40). More recently, psychological trauma has been identified as a risk factor for AD as well (41).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of PDE4A from spines with advancing age leads to dysregulation of cAMP-Ca 2+ signaling and increased kinase phosphorylation of tau in pyramidal cell circuits. However, it has long been appreciated that head injury is also a significant risk factor for AD (39) as well as CTE (34,40). More recently, psychological trauma has been identified as a risk factor for AD as well (41).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] What is less clear is whether mild TBI can also lead to cognitive impairment, with several studies showing negative results. [19][20][21] More than one million concussions occur annually in this country, with 300,000 resulting from sports-related activities.…”
Section: Discussionmentioning
confidence: 99%
“…Well over 10 million Americans are expected to have the condition by 2050 as the population continues to age. 9 Many risk factors are well-characterized, including age and family history, 10 -14 whereas many others are under investigation, including education level, 15,16 head trauma, 17,18 high blood pressure, 19 caloric intake, and high cholesterol. 20,21 Regarding genetic factors, rare mutations on genes coding for amyloid precursor protein, presenilin 1, and presenilin 2 have been identified that are deterministic for early-onset AD.…”
mentioning
confidence: 99%